MENINGKATKAN KEMAMPUAN PENALARAN DAN KOMUNIKASI MATEMATIS SISWA SMA MELALUI PENDEKATAN KONTEKSTUAL BERBANTUAN PROGRAM AUTOGRAPH - Koswara, Ucu (2012)
This paper presents the findings from a pretest-posttest experimental control group design conducted by using contextual teaching approach assisted with autograph program to investigate students' mathematical reasoning and communication abilities.The study involved 70 grade-10 students in Tasikmalaya district. The instrumens in this study are mathematical reasoning and mathematical communication abilities tests, and opinion scale. The study found that: a) Mathematical reasoning ability of students taught by contextual teaching approach assisted with autograph program was better than that of students taught by conventional teaching. However, there was difference between mathematical communication ability of students taught by contextual teaching approach assisted with autograph program and of students taught by conventional teaching; and both abilities were classified as mediocore; b) There was high associatian between mathematical reasoning and communication abilities; c) Students performed positive opnion toward contextual teaching approach assisted with autograph program.